명시적 제시와 암시적 제시가 심리동사의 분사형 학습에 미치는 영향 - 이정은; Jung Eun Lee (중등영어교육, 2008)
Psychological verbs in English are one of the most difficult grammar items for Korean learners. Thus, the purpose of this study is to explore how well Korean EFL learners understand participles of English psychological verbs when they are taught by explicit grammar teaching and implicit grammar teaching. One hundred students participated in this study and they were divided into Four groups according to their English ability: two high level groups and two low level groups. All groups were tested twice; before they were taught and after the experiment finished. The major findings are as follows: First, the result showed that the high-level learners who were taught by implicit teaching were able to acquire more exact meaning of the psychological verbs than who were taught by explicit teaching. However, whether they were taught by explicit or implicit teaching, they still had difficulty using participles of psychological verbs in the context. Second, low-level learners who didn``t know even the exact meaning of the psychological verbs were able to acquire the meaning when they were taught by implicit teaching. In addition, they also improved their ability of using the proper participle of the psychological verbs in the context after the implicit teaching. Finally, the result for understanding learner``s variable showed that lowlevel learners were little interested in English. Almost more than half learners among them hated English subject. This problem may affect their studying English, so English teachers should prepare for various activities and materials for them when they teach students psychological verbs.